Strain Improvement Via Random Mutation For Glucoamylase Production By Aspergillus Niger Van Tieghem Through Solid State Fermentation - Murugaiah, Hemalatha (2012)
Glucoamylase enzyme is widely utilized for conversion of starch into glucose during saccharification process. Aspergillus niger van Tieghem is commonly used for glucoamylase production in submerged cultivation system (SmF) and solid state fermentation (SSF). This research was carried out to enhance glucoamylase production by mutating A. niger van Tieghem using chemical mutagen, ethyl methane sulphonate (EMS) via random mutation. Mutant ANC9 was identified as a potential mutant which produced, 1.9 and 1.6 fold higher glucoamylase activity towards cooked starch and raw starch respectively in SmF using cooked starch as substrate. Glucoamylase activity towards raw starch and cooked starch in SSF by mutant ANC9 were 44.81± 1.2 Ulg and 101.50 ±2.2 Ulg respectively compared to wild strain which was only able to produce 34.4±O.5 Ulg towards cooked starch and 79.1±2.2 Ulg towards raw starch.